The effect of Li4Ti5O12 nanoparticles on structural, linear and third order nonlinear optical properties of PVDF films. (17th May 2019) - El-Metwally, E G; Nasrallah, D A; Fadel, M
Abstract: Casting technique is used to prepare Polyvinylidene fluoride (PVDF) nanocomposite films doped with different concentrations (0, 0.5, 1, 1.5 and 2 wt%) of Li4 Ti5 O12 NPs. The structure of the studied films was examined using x-ray diffraction (XRD) and Fourier transformer infrared (FTIR). The crystalline features shown by XRD spectra are attributed to the PVDF matrix. This indicates that low concentrations of Li4 Ti5 O12 were completely dispersible. Data obtained from FTIR showed that there is interaction between PVDF matrix and Li4 Ti5 O12 NPs. The optical properties of PVDF/Li4 Ti5 O12 nanocomposites were studied using the measurements of absorbance A ( λ ) and transmittance T ( λ ) in the wavelength range from 190 to 800 nm. The allowed transitions for the studied nanocomposites are indirect and direct transitions. The optical band gap E g o p t of pure PVDF decreases from 3.625eV to 1.005 eV for indirect transitions and from 5.567 eV to 4.858 eV for direct transitions as Li4 Ti5 O12 content increased from (0 wt%) to (2 wt%). The Urbach energy E u increases with increasing Li4 Ti5 O12 content. The refractive index n, extinction coefficient k, dielectric constant ε 1 and loss ε 2 of the films were calculated. Also, the optical parameters E o, E d, n ∞, λ o, S o and ε ∞ loss ε 2 were estimated and discussed according to the model of Wemple-DiDomenico. The dispersion of n for pure PVDF and PVDF-doped with Li4 Ti5 O12 NPs follow the model of single oscillator. Third order nonlinear optical susceptibility χ ( 3 ) and nonlinear refractive index n 2 were analyzed by spectroscopic method.